PENINGKATKAN HASIL BELAJAR DENGAN MEMANFAATANKAN GREEN HOUSE PADA PEMBELAJARAN PRODUKTIF ATPH MATERI AGRIBISNIS TANAMAN SAYURAN: SMKN 2 SITUBONDO - SUSIANA SUSIANA (Mitra Pendidikan, 2023)
This classroom action research aims to improve the learning outcomes of class XII ATPH.1 students of SMK Negeri 2 Situbondo by utilizing green houses in ATPH productive learning on vegetable agribusiness material This researcher used a qualitative approach because in taking action on research subjects, what was prioritized was expressing meaning; namely the meaning and process of learning as an effort to increase motivation, enthusiasm and learning achievement through actions taken (Wahid Murni et al. 2010). The type of research used was school action research (PTK). This school action research was carried out at SMK Negeri 2 Situbondo which is located at Jl. Talkandang No.1, Talkandang East, Talkandang, Kec. Situbondo, Situbondo Regency, East Java postal code 68315. This research was conducted for 3 months, namely in January 2020 in March 2020. The research subjects were students of class XII ATPH-1 SMK Negeri 2 Situbondo in the even semester of the 20198/2020 academic year, with a total students as many as 32 students Sources of data in this study are 1). Learners 2). List of Daily Deuteronomy Values ​​3). Student Response Questionnaire and, 4). Observation Result Sheet. The data collection technique used in this study was carried out through 1). documentation, 2). observation, 3). questionnaire, 4. written and 5). document analysis. Analysis of the data used in this class action research using descriptive analysis includes 1). qualitative descriptive analysis and, 2). comparative descriptive analysis. An indicator of the success of classroom action research in this class is said to be successful if at least 75% of students have reached the completion limit, namely a score of 78 with a minimum class average score of 78 on daily tests on vegetable agribusiness material Based on the description in the discussion, it can be concluded that the use of Green House in learning Vegetable Agribusiness can improve student learning outcomes. From the research it was revealed that there was an increase in student learning outcomes through the use of Green Houses in learning Vegetative Plant Breeding. The increase in student learning outcomes in cycle 1 and cycle 2 was 68 and 70. The percentage increase in the number of students who achieved KKM in the initial conditions, cycle 1 and cycle 2 were respectively: 64%, 69%, and 78%.